1919 Me. Acts 235 - (:unkn) unknown (My University, 1919)
Swivel, pivot and set gun added to prohibited devices; penalty for violation increased to $100 and costs and imprisonment for sixty days for possession, ch. 196, § 25: No person shall have in possession at any time when he is upon the wild lands, water or highways, or in the woods or fields of the state, or in any camp, lodge, or place of resort for hunters or fishermen, or in its immediate vicinity, any jacklight or light fitted for use in the hunting of game in the night time, or any swivel, pivot, or set gun...
Keywords: HUNTING REGULATION; TRAP GUNS